Hubungan Status Gizi Dan Riwayat Imunisasi PCV Dengan Kejadian Pneumonia Pada Balita Di Rumah Sakit Dr. M. Yunus Kota Bengkulu Tahun 2025 - Neni Suci Herpinta; Kintan Anissa; Bella Anarkie (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Pneumonia is an acute inflammation of lung tissue caused by microorganisms (bacteria, fungi, and viruses), which can present symptoms ranging from mild to severe. Several factors contribute to the occurrence of pneumonia, including nutritional status and PCV immunization history. In cases of malnutrition, immune status is impaired, making individuals more susceptible to infections that can lead to pneumonia in toddlers, ranging from mild to severe. Pneumococcal vaccine (PCV) is an important vaccine administered to protect toddlers from infections caused by Streptococcus pneumoniae bacteria. Objective: This study aims to determine the relationship between nutritional status and PCV immunization history with the incidence of pneumonia at Dr. M. Yunus Hospital, Bengkulu City. Method: This research employs a quantitative method with a cross-sectional design. The population consists of all children receiving treatment at Dr. M. Yunus Hospital. A sample of 52 toddlers was taken using purposive sampling techniques. Data analysis was conducted using the Chi-Square test. Results: All toddlers with poor and very poor nutritional status (100%) experienced pneumonia. The bivariate analysis using the Chi-Square test yielded a p-value of 0.000 (p < 0.05), indicating a significant relationship between nutritional status and the incidence of pneumonia. Additionally, PCV immunization was also found to have a significant relationship with the incidence of pneumonia in toddlers. Almost all toddlers (94.6%) who did not receive complete PCV immunization experienced pneumonia. The Chi-Square test showed a p-value of 0.000 (p < 0.05). Conclusion: There is a significant relationship between nutritional status and PCV immunization history with the incidence of pneumonia in toddlers. Recommendation: There is a need to increase the coverage of PCV immunization and improve nutritional status in toddlers as a preventive measure against pneumonia in a timely and sustainable manner.